Type IV codes over a non-local non-unital ring - Alahmadi,Adel (Universidad Católica del Norte, Departamento de Matemáticas, 2020)
Abstract: There is a local ring H of order 4, without identity for the multiplication, defined by generators and relations as H =〈a, b | 2a = 2b = 0, a 2 = 0, b 2 = b, ab = ba = 0〉. We classify self orthogonal codes of length n and size 2 n (called here quasi self-dual codes or QSD) up to the length n = 6. In particular, we classify quasi Type IV codes (a subclass of Type IV codes, viz QSD codes with even weights) up to n = 6.